The Activity of Giuseppe Fontana within Grand Duchy of Lithuania - Kaladžinskaitė, Auksė (Actual Problems of Theory and History of Art, 2013)
The purpose of an article is to introduce new facts of biography and art of Italian architect Giuseppe Fontana. Overviewed facts and Fontana‘s creative legacy allow us to access the architect’s contribution to the development of architecture of the Grand Duchy of Lithuania in the 18th c. and assert that along with Johann Christoph Glaubitz he was one of the most productive and famous architects of his environment.
Keywords: Giuseppe Fontana; Grand Duchy of Lithuania; Vilnius; Vitebsk; Late Baroque; 18th c; architectural commission; Italian architect; the Ogiński family